Newsgame aplicado ao ensino de jornalismo: uma proposta de guia informativo para docentes - RIBEIRO, Mayave Carolina da Silva (Universidade Federal do Pará, 2023)
The product, called Start Game, was developed as a proposal for an informative guide about Newsgame for Journalism teachers. The informative guide was hosted in a free virtual environment that converges multimidia didactic materials and presents Newsgames as a teaching-learning tool. The study that originated the product was due to personal experiences lived in the classroom by this author and, from questions about the teaching of the disciplines of the Journalism course, the inspiration for the research emerged. From such inquietudes, the research on how the pedagogical curricula are used in the courses brought information that indicated that, as time went by, the National Curricular Guidelines, which govern the pedagogical curricula, prioritize an increasingly balanced involvement of theoretical and practical class, that is, students should be offered both theoretical and humanistic supporte, as well as support focused on the professional daily routine. As the research continued, the Newsgames (games based on news and real events) were found, by studying their structure and how they are developed, and an opportunity was seen to present to Journalism course teachers a teaching approach based on this type of game. Thus, the study intended to develop a product that indicates how Journalism teachers can use Newsgames as a strategic tool for teaching journalism, so that the product fits as an initiation artifact to the theme, reinforcing the potential of Newsgames for meaningful teaching. To this and, the study presents characteristics of Newsgames that qualify them as didactic resource that promotes meaningful teaching, make it more attractive to students, as well as the enrichment of teaching activities through gamification, which enables the engagement and protagonism of students in their learning process. Thus, a final product was developed in the format of an informative guide for Journalism teachers, called Start Game.